Thermoforming Process for Fabricating Oral Appliances: Influence of Heating and Pressure Application Timing on Formability - Junko Yamada, DDS; and Yoshinobu Maeda, DDS, PhD (Journal of Prosthodontics, 2007)
This study was designed to examine the influence of heating and pressure application timing for thermoplastic soft materials on formability during the thermoforming process.